Analysis of Serum Levels of IgA Antibodies to Epstein Barr Virus Capsid Antigens in the Spouses and the Children of Patients with Nasopharyngeal Carcinoma - Jiru CHENG; Yonglin CAI; Yuming ZHENG (Cancer Biology & Medicine, 2009)
OBJECTIVE To analyze the serum levels of IgA antibodies to Epstein Barr virus capsid antigens (EBV/IgA/VCA) in patients with nasopharyngeal carcinoma (NPC) and in their spouses and children in order to further evaluate the risk of developing the disease in family members of NPC patients. METHODS Four categories of sera were used to detect EBV/ IgA/VCA using the immunoenzyme method. In our study 317 biopsy-con fi rmed NPC patients, 317 spouses and 317 children of the NPC patients, as well as 413 healthy subjects as the controls that came from the same area were enrolled. RESULTS The positive rate of EBV/IgA/VCA was 97.2%, 14.2%, 19.9% and 3.1% in the NPC patients, the spouse and child groups, and in the control group, respectively. The positive rate was significantly higher in the NPC group than in the other 3 groups, and it was also significantly higher in the spouse and in the child groups than in the control group (P < 0.001). The results of the relative to identified distribution unit (Ridit) analysis showed that the average Ridit values were 0.860, 0.404, 0.424 and 0.356 respectively in the NPC patients, in the spouse and child groups, and in the control group. The antibody titer of IgA/VCA was significantly higher in the NPC group than in the other 3 groups, and it was also signifi cantly higher in both the spouse and child groups than in the control group (P < 0.001). The OR values of positive EBV/IgA/VCA antibody were 5.09 and 7.63, respectively in the spouse and child groups. No significant differences were found in the positive rates or in the titers of IgA/VCA antibody between the groups of spouses and children (P > 0.05). CONCLUSION Positive detection of EBV/IgA/VCA antibody occurs in familial aggregation, as there is ample opportunity for EBV reactivation in the spouses and in the children of NPC patients. These individuals with a high risk of developing the NPC should be closely followed in order to detect the disease at an early stage.